2021
DOI: 10.1111/ijac.13741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal stability of Mn+1AXn phases on microstructure and mechanical properties of Mn+1AXn/ZA27 composites

Abstract: Special layered structure endows ternary M n+1 AX n phase ceramics with good electrical and thermal conductivity, excellent abrasive resistance, and perfect thermal shock resistance. In this work, three kinds of M n+1 AX n phase ceramics (Ti 3 SiC 2 , Ti 3 AlC 2 , and Ti 2 SnC) were chosen to reinforce the ZA27 alloys, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Ti 3 SiC 2 is a typical member of MAX phase with a ternary layered structure. It possesses combination characteristics of metal and ceramic, [1][2][3] such as good electrical and thermal conductivity, relatively low hardness, high specific strength, excellent high-temperature mechanical properties, and good corrosion resistance; thus, it was widely used in high-temperature environments, chemically resistant environments, and functional materials fields. [4][5][6][7][8] JOVIC et al found that Ti 3 SiC 2 was relatively stable and passivated in the HCl, H 2 SO 4 , and NaOH solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 3 SiC 2 is a typical member of MAX phase with a ternary layered structure. It possesses combination characteristics of metal and ceramic, [1][2][3] such as good electrical and thermal conductivity, relatively low hardness, high specific strength, excellent high-temperature mechanical properties, and good corrosion resistance; thus, it was widely used in high-temperature environments, chemically resistant environments, and functional materials fields. [4][5][6][7][8] JOVIC et al found that Ti 3 SiC 2 was relatively stable and passivated in the HCl, H 2 SO 4 , and NaOH solutions.…”
Section: Introductionmentioning
confidence: 99%